WEB 2.0 USAGE IN HIGHER EDUCATION IN SOUTH AFRICA - Hough, Johan; NEULAND, ERNST (South African Journal of Higher Education, 2016)
The proliferation of Web 2.0 applications in general and in higher education in particular was the impetus for this survey-based research into practices that online users (students) currently employ when using Web 2.0 sites. As part of the study, the popularity of Web 2.0 technologies and sites among online users at two universities were investigated to determine the extent of access and use as well as the potential threat to users of Web 2.0. The results of this study indicate that the use of Web 2.0 sites is very popular among both on-campus (full-time) and distance learning (part-time) students, but that modes of study and the site of access differ significantly between the groups. The respondents indicated that they regularly visit Web 2.0 sites, and that all of them (100%) post personal information on these sites. Both types of users are acutely aware of the risks associated with the technology and posting of information on these sites, and are alert regarding the possibility of internet theft and phising attacks. Given the distinctive characteristics of the two groups of students, significant differences were observed between the full-time and part-time users in terms of mode of study, influence of online technologies on studies, and their ranking of potential risks, all of which pose unique academic challenges for students, educators and institutions of Higher Education in South Africa.